Determination of maximum pvc reclaimed material content in pvc soles compound, observed from tehno economics point of view - Susilowati et. al., Susilowati (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1988)
The objectives of the study is to obtain a formula of soles compound, by determining the content of maximum PVC reclaimed material added into the batch, observed from the view point of economic study, which means to obtain a soles compound formula, the physical properties of which meet the SII 1103 â 84 Sol Lentur Cetak PVC (moulded flexible PVC soles), which produces low price soles.Â Â Â Â Â Â Â Â Â The research is emphasized on variation of volume ofÂ PVC reclaimedÂ material added into the batch, based on SII 1103 -84. The result of this research shows that composition of different compound produces different melting point as well.Â Â Â Â Â Â Â Â Â Where as the volume of maximum PVC reclaimed material added into the batch is 40%, and it is found from economic study that soles compound which contains 40 % PVC reclaimed material and 60 % non PVC reclaimed material ( consist of PVC 100% , SOP 60%, epoxy 6%, Ba Cd Zn 2%, CaCO3 10 % Carbon black 0,05%). Produces the best soles that is good physical properties and cheap price ( Rp. 552,85/pair).Â